Question and Answers Forum

All Questions      Topic List

Arithmetic Questions

Previous in All Question      Next in All Question      

Previous in Arithmetic      Next in Arithmetic      

Question Number 211979 by Spillover last updated on 25/Sep/24

Answered by BHOOPENDRA last updated on 25/Sep/24

∫(dx/((x^2 tan^(−1) x+tan^(−1) x +x^2 π+π)))  ∫(dx/((x^2 +1)(tan^(−1) x+π)))  Let  t=tan^(−1) x+π           dt=(dx/(1+x^2 ))  ∫ (1/t)dt= ln(t)   put t=(tan^(−1) x +π)  ln(tan^(−1) x+π)+c

dx(x2tan1x+tan1x+x2π+π)dx(x2+1)(tan1x+π)Lett=tan1x+πdt=dx1+x21tdt=ln(t)putt=(tan1x+π)ln(tan1x+π)+c

Commented by Spillover last updated on 26/Sep/24

great.thanks

great.thanks

Terms of Service

Privacy Policy

Contact: info@tinkutara.com